Total thyroidectomy versus thyroid lobectomy for papillary thyroid cancer: Comparative analysis after propensity score matching: A multicenter study. (February 2017) - Kuba, Sayaka; Yamanouchi, Kosho; Hayashida, Naomi; Maeda, Shigeto; Adachi, Toshiyuki; Sakimura, Chika; Kawakami, Fusako; Yano, Hiroshi; Matsumoto, Megumi; Otsubo, Ryota; Sato, Shuntaro; Fujioka, Hikaru; et al.
Abstract: Background: In patients with papillary thyroid carcinoma (PTC), the role of total thyroidectomy (TT) versus that of thyroid lobectomy (TL) has been controversial. Methods: This retrospective study was approved by our institutional review board, and the requirement to obtain informed consent was waived. In total, 173 patients with 1- to 5-cm stage cN0 and cM0 PTC tumors treated by curative surgery from 1994 to 2008 were evaluated. Clinicopathologic features and adverse events were compared between patients who underwent TT and those who underwent TL. After adjustment for differences in baseline clinicopathologic factors using propensity score matching, we compared recurrence-free survival (RFS) and OS. Results: TL was performed in 120 patients and TT in 53 patients. Patients who underwent TT were older; had larger tumors; more frequently had nodal metastasis, multifocal tumors, and extracapsular invasion; and more frequently underwent radioactive iodine ablation than patients who underwent TL. Hypocalcemia requiring medication and recurrent laryngeal nerve paralysis were more frequent in TT than TL. The 10-year RFS and OS of all patients were 93.3% and 96.7%, respectively. There was no significant difference in RFS (90.6% vs 93.0% in TT and TL groups, respectively) or OS (96.2% vs 96.9% in TT and TL groups, respectively) according to the extent of surgical resection after propensity score matching. Conclusion: Equivalent prognoses were observed for patients with 1- to 5-cm stage cN0 and cM0 PTC tumors treated by TL or TT after propensity score matching. Adverse events occurred less frequently in patients who underwent TL than TT. Highlights: 173 patients with 1 to 5 cm stage cN0, cM0 papillary thyroid carcinoma treated by curative surgery were evaluated. Thyroid lobectomy (TL) was performed in 120 patients and total thyroidectomy (TT) in 53 patients. Equivalent prognoses were observed for PTC patients treated by TL or TT after propensity score matching. Hypocalcemia and recurrent laryngeal nerve paralysis were more frequent in TT than TL.